2016
DOI: 10.1111/joor.12394
|View full text |Cite
|
Sign up to set email alerts
|

Taste detection ability of elderly nursing home residents

Abstract: Due to the rapid rise of aged populations throughout the world, it is essential to elucidate the cause of taste dysfunction, because it may reduce appetite, leading to inadequate dietary intake. We aimed to compare taste detection ability between dependently and independently living geriatric individuals of nearly the same age with oral status. Forty-three elderly individuals considered to be cognitively eligible and residing in nursing homes in Japan were enrolled (n = 43, 82·3 ± 8·5 years) and were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Behavioural or lifestyle variables have also been shown to play a major role in taste‐related sensations as people age. Commonly reported behavioural influences expressed in later life include changes in food intake (preferences and appetites) , smoking history (deleterious effects of tobacco smoking on worsening taste perception) , oral hygiene (poor self‐care is correlated with taste loss) and institutionalisation (changes in taste sensation among those living in high‐care settings) . Among these factors, the negative effects associated with institutionalisation on changing taste sensation represent a promising area of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural or lifestyle variables have also been shown to play a major role in taste‐related sensations as people age. Commonly reported behavioural influences expressed in later life include changes in food intake (preferences and appetites) , smoking history (deleterious effects of tobacco smoking on worsening taste perception) , oral hygiene (poor self‐care is correlated with taste loss) and institutionalisation (changes in taste sensation among those living in high‐care settings) . Among these factors, the negative effects associated with institutionalisation on changing taste sensation represent a promising area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Older people are more likely to suffer from multiple chronic diseases, with higher intakes of medication . The diseases and the living situation of institutionalised older adults are more likely to cause of the decreased taste sensitivity . Additionally, decreased taste sensitivity was observed in hospitalised older people potentially due to advanced age, polypharmacy and poor nutrition .…”
Section: Behavioural Specificities and Taste Sensation In Older Adultsmentioning
confidence: 99%
“…Humans are able to detect various tastes by stimulation of receptors in taste buds in oral mucosa, which is important for personal assessment of the safety, quality and nutritional value of foods. Several factors have been suggested to be associated with taste loss or dysfunction, including ageing, medication, malnutrition, smoking, hospitalisation and institutionalisation (1)(2)(3). To detect a compound dissolved in water, Mojet et al reported that older subjects required a higher concentration than younger subjects (4).…”
Section: Introductionmentioning
confidence: 99%